KELEMBAGAAN PENYULUHAN PERTANIAN DI PROVINSI RIAU - Yulia Andriani; Kausar '; Cepriadi ' (Fakultas Pertanian, Universitas Riau, 2015)
Extension Institution is a government agency and or community has the duty and the function of organizing counseling. This study aims describe the institutional model of extension in the province of Riau. This research is a descriptive study conducted in Kampar and Kuantan Singingi District at Riau Province in May-November 2015. The data used in this study are primary and secondary data. Primary data were obtained through a structured interview method using questionnaires and focus group discussion. Samples in this study was the head of the work unit, coordinator of outreach and extension. The sample selected by purposive sampling method. Implementation of agricultural extension in Kampar regency is under Badan Pelaksana Penyuluhan dan Ketahanan Pangan (BPPKP). While in Kuantan Singingi, carried out by dinas tanaman pangan, dinas perkebunan, dinas perikanan, dinas peternakan and dinas kehutanan. The model of agricultural extension at Kampar Regency with polivalent and at Kuantan Singingi with monovalent extension.